Using the Analytical Hierarchy Process (AHP) to Construct a Measure of the Magnitude of Consequences Component of Moral Intensity - Stein, Eric W. (Journal of business ethics, 2009)
The purpose of this work is to elaborate an empirically grounded mathematical model of the magnitude of consequences component of “moral intensity” (Jones, Academy of Management Review 16(2),366, 1991) that can be used to evaluate different ethical situations. The model is built using the analytical hierarchy process (AHP) (Saaty, The Analytic Hierarchy Process, 1980) and empirical data from the legal profession. One contribution of our work is that it illustrates how AHP can be applied in the field of ethics. Following a review of the literature, we discuss the development of the model. We then illustrate how the model can be used to rank-order three well-known ethical reasoning cases in terms of the magnitude of consequences. The work concludes with implications for theory, practice, and future research. Specifically we discuss how this work extends the previous work by Collins (Journal of Business Ethics 8, 1, 1989) regarding the nature of harm variable. We also discuss the contribution this work makes in the development of ethical scenarios used to test hypotheses in the field of business ethics. Finally, we discuss how the model can be used for after-action review, contribute to organizational learning, train employees in ethical reasoning, and aid in the design and development of decision support systems that support ethical reasoning.